2014
DOI: 10.1039/c4ta03409k
|View full text |Cite
|
Sign up to set email alerts
|

Thermochemical heat storage based on the Mn2O3/Mn3O4redox couple: influence of the initial particle size on the morphological evolution and cyclability

Abstract: Thermochemical energy storage (TCS) based on reduction-oxidation cycles of multivalent metal oxides is of great interest for concentrating solar facilities, as it can allow enhancing the global plant efficiency and improving the energy generation dispatchability. However, to guarantee the feasibility of the process, selected materials should present long term durability, which requires the evaluation of the redox couple cyclability. In this work we have demonstrated, for the first time, the suitability of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
81
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 116 publications
(85 citation statements)
references
References 29 publications
(61 reference statements)
3
81
0
1
Order By: Relevance
“…In our previousw ork, [9] we concluded that reduction was limited by heat transfer,w hereas oxidation appeared to be controlled by diffusional phenomena and we attributed the decreaseo ft he reoxidation rate to sintering. In this respect, chemicalo rm icrostructural modificationso fr aw manganese sesquioxide are considered as the two main options to improve the redox properties of the Mn 2 O 3 /Mn 3 O 4 pair.D oping with other metals has been generally studied as af irst approach as the incorporation of cations of different oxidation states andr adii could create chargei mbalances, disorders, or vacancies that are beneficial for oxygen diffusion through the crystal lattice.H owever,i th as not alwaysb een efficient.…”
Section: à1 ð3þmentioning
confidence: 91%
See 2 more Smart Citations
“…In our previousw ork, [9] we concluded that reduction was limited by heat transfer,w hereas oxidation appeared to be controlled by diffusional phenomena and we attributed the decreaseo ft he reoxidation rate to sintering. In this respect, chemicalo rm icrostructural modificationso fr aw manganese sesquioxide are considered as the two main options to improve the redox properties of the Mn 2 O 3 /Mn 3 O 4 pair.D oping with other metals has been generally studied as af irst approach as the incorporation of cations of different oxidation states andr adii could create chargei mbalances, disorders, or vacancies that are beneficial for oxygen diffusion through the crystal lattice.H owever,i th as not alwaysb een efficient.…”
Section: à1 ð3þmentioning
confidence: 91%
“…As commented before, we attributedt he cycleto-cycle decay on the oxidation rate to oxygen diffusion hindrance caused by sintering, [9] although this does not apply to the reduction, as reduction values were stable over cycling as this reaction was limited by heat transfer.The heat-transfer-limited nature of the reduction reaction of metal oxides has been reported previously in the case of ceria. [25,26] The reduction of undoped Mn 2 O 3 (0F) also followed such behavior ( Figure 8A): the faster the heating rate, the faster the reduction.…”
Section: Effect Of the Incorporation Of Fe On The Redox Kineticsmentioning
confidence: 91%
See 1 more Smart Citation
“…The general pathway of TCS based on metal oxides is: There are various concepts that could be used to implement the TCS in Concentrating Solar Power (CSP) plants. Solutions proposed by Agrafiotis 12 , or assumed by Carrillo 13 and Álvarez de Miguel 14 for their investigations are based on indirect storage systems. The solid metal oxide is retained into a storage tank or a particle reactor where the charging phase takes places by absorbing heat from a hot air stream coming from the solar receiver.…”
Section: Introductionmentioning
confidence: 99%
“…Co 3 O 4 /CoO and Mn 2 O 3 /Mn 3 O 4 [1][2][3] with porous ceramic structures in order to effectively store solar heat in air-operated Solar Tower Power Plants has been set forth and tested in lab-scale in a series of previous publications [4][5][6][7]. If such oxides are coated on porous heat exchange modules, solar heat produced during on-sun operation can be used to power the endothermic reduction of the oxide (forward reactions of exemplary schemes 1, 2 below); the thermal energy can be entirely recovered by the reverse exothermic oxidation reaction during off-sun operation.…”
Section: Introductionmentioning
confidence: 99%